In vitro Antimicrobial Evaluation of Ortho-/meta-Alkoxyphenylcarbamic acid esters containing 4-(Pyrimidin-2-yl)piperazin-1-yl Moiey - Malik, Ivan; Sedlarova, Eva; Bukovsky, Marian; Csollei, Jozef; Stanzel, Lukas; Sichrovska, Lubica (Dhaka University Journal of Pharmaceutical Sciences, 2015)
Abstract not available DOI: http://dx.doi.org/10.3329/dujps.v13i2.21903 Dhaka Univ. J. Pharm. Sci. 13(2): 215-219, 2014 (December)